Performance-Oriented Application Development for Distributed Architectures. - M. Gerndt (IOS Press, 2002)
This publication is devoted to programming models, languages, and tools for performance-oriented program development in commercial and scientific environments. The included papers have been written based on presentations given at the workshop PADDA 2001. The goal of the workshop was to identify common interests and techniques for performance-oriented program development in commercial and scientific environments. Distributed architectures currently dominate the field of highly parallel computing. Distributed architectures, based on Internet and mobile computing technologies, are important target architectures in the domain of commercial computing too. The papers in this publication come from the two areas: scientific computing and commercial computing.